Relative peripheral refraction across 4 meridians after orthokeratology and LASIK surgery - Queirós, A. (2018)
Background: To characterize the axial and off-axis refraction across four meridians of the retina in myopic eyes before and after Orthokeratology (OK) and LASIK surgery. Methods: Sixty right eyes with a spherical equivalent (M) between − 0.75 to − 5.25 D (cylinder <− 1.00 D) underwent LASIK (n = 26) or OK (n = 34) to treat myopia. Axial and off-axis refraction were measured with an open-field autorefractometer before and after stabilized treatments. Off-axis measurements were obtained for the horizontal (35° nasal and temporal retina) and vertical (15° superior and inferior retina) meridians, and for two oblique directions (45–225° and 135–315°) up to 20° of eccentricity. The refractive profile was addressed as relative peripheral refractive error (RPRE). Results: OK and LASIK post-treatment results showed an increase of myopic relative refraction at several eccentric locations. At the four meridians evaluated, the M component of the pre-treatment RPRE values was not statistically different (p > 0.05) from the post-treatment RPRE within 30° and 20° of the central visual field after LASIK and OK, respectively. These results demonstrated that the treatment zone warrants an optimal central field of vision. Conclusions: The present study gives an overview of RPRE after refractive corneal reshaping treatments (OK and LASIK) across vertical, horizontal and two oblique meridians together. This allows a 3D representation of RPRE at the retina and shows that the myopic shift induced by both treatments is more relevant in horizontal directions.